Toxicity and Degradation of Animal Antibiotic Residue in Soil - Yan, Wang (2010)
Antibiotics are widely used in farm animals especially pig and poultry, however,they are poorly absorbed by the animals and entered the environment mainly via the application of manure for crops production. This thesis aimed to i) investigate the status of the use of antibiotic by pig and poultry farmers in Malaysia, ii) evaluate the environmental risks when manures contaminated by antibiotic are used as fertilizer in soils and iii) propose a possible method to accelerate the degradation of antibiotic in the environment. To achieve the first objective, a survey on the use of the antibiotics by Malaysian pig and poultry farmers was conducted. The results indicated that tetracyclines (TCs) and sulfanimines (SAs) were the most widely used antibiotics in the Malaysian pig and poultry farms. Among the highest concentrations detected in the diets were 51,948.5 and 28,791.1 ng/g of sulfamethazine in diets of grower pigs and broilers, respectively, while in the fecal samples collected, 130.0 ng/g sulfamethazine and 129.2 ng/g chlortetracycline were detected in the finisher pigs and 380.4 ng/g sulfamethazine in grower broilers. To evaluate the environmental risks of antibiotic residues in the soil-plant system, three experiments were carried out. The first experiment examined the effect of different concentrations of TCs and SAs on the environmentally beneficial bacteria, and Shewanella decolorationis S12 was used as the model bacteria for the study. The results showed that the antibiotics significantly inhibited Fe (III) reduction and dye decoloration activities of S. decolorationis S12 in the reduction system. The above inhibition was suggested to be due to a decrease in live S. decolorationis S12 population and/or modifications of their cell structures in the presence of antibiotics. The second experiment studied the effects of sulfadiazine (SD) residues on soil nitrogen mineralization and soil microbial community. The results showed that SD significantly inhibited the mineralization of N and microbial parameters including ammonifying and nitrifying bacteria population, microbial biomass N, urease and nitrate reductase and soil microbial communities activities, however, the activities of soil microbial communities can be used as the sole indicator to monitor changes of soil N mineralized under SD pollution. The third experiment investigated the toxicity effects of SD residues on vegetable lettuce. The results clearly showed that SD were absorbed and accumulated in the different organs of the lettuce and adversely affected their growth. It is suggested that high concentrations of SD caused physiological damages to roots of the lettuce, allowing easy translocation of SD from the roots to the leaves and caused damages to the leaf cells and thus prohibited photosynthesis. A goethite (-FeOOH)-oxalate Fonten-like system was evaluated to accelerate the photodegradation of antibitotics under UV irradiation. The results indicated the optimal pH value and initial concentration of oxalic acid in the system were 3.5 and 4.0 mM, respectively. The eco-toxicity of the intermediate products was found to be lower than the mother SD compound, thus suggesting the positive effect of photodegradation on the impact of SD on the environment. These results can help to better understand the natural degradation of SD (possibly other antibiotics as well) and offer the possibility of treating effluents, including livestock wastewater, contaminated with antibiotics at low cost since goethite, oxalate and light exist in natural environment.